Minigrow: A Smart Solution to Improve Household Food Security in Pudak Village - Sri Arnita Abu Tani; Fachroerrozi Hoesni; Olfa Mega; Zulfa Elymaizar; Rayandra Ashyar; Husda Marwa (Journal of Saintech Transfer, 2026)
Pudak Village is an Integrated Laboratory Village (Desa Laboratorium Terpadu/DLT) of the University of Jambi and serves as a center for agricultural, livestock, and fisheries activities. However, frequent flooding during the rainy season often reduces agricultural productivity and household income. To address this issue, a Minigrow Farm program was implemented to improve household food security and generate additional income through integrated small-scale vegetable cultivation and poultry farming. The program involved four housewives from the local Women Farmers Group (KWT) who had available yard space. Their home yards were converted into productive areas for growing vegetables, including pak choi, mustard greens, water spinach, and red spinach, and for raising laying hens. Activities were conducted using a learning-by-doing approach, consisting of two months of mentoring followed by two months of independent implementation. The results showed that vegetable production generated a total income of IDR 3,066,000 from two production cycles per month, while egg sales from 55 laying hens generated IDR 2,970,000 per month. The combined additional income reached IDR 6,036,000 for the four participating households. Participants also demonstrated improved knowledge and skills in integrated farming practices. The Minigrow Farm model effectively enhanced household food security, increased family income, and promoted sustainable use of household yard resources in flood-prone rural areas.